A high hardness bar for a ship and a method of manufacturing the same

CN122918673APending Publication Date: 2026-10-16BAOJI JUXINYUAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611416952.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

单纯的微弧氧化处理,其生成的陶瓷氧化膜层存在微孔缺陷,海水中氯离子易沿孔隙侵入基体,易诱发点蚀;而单一等离子渗氮,又会使得氮化层过硬,容易出现脆裂等问题

Benefits of technology

1、本发明通过对钛棒进行微弧氧化处理,在其表面生成陶瓷氧化膜;陶瓷氧化膜具有比钛棒更高的硬度,同时还具有优异的耐腐蚀性能,可以显著提高钛棒的硬度和耐腐蚀性能。本发明中所用的微弧氧化电解液中还加入了硝酸铈,在陶瓷氧化膜中引入稀土金属铈,可以起到细化陶瓷膜晶粒,提高陶瓷氧化膜的表面质量的作用,对于钛棒的硬度和耐腐蚀性能有着积极促进作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of titanium alloy surface treatment, in particular to a high-hardness rod for ships and a preparation method thereof.S1: taking a titanium rod as a base material, polishing the surface of the titanium rod, removing oil, pickling, and obtaining a pretreated titanium rod;S2: immersing the pretreated titanium rod into a micro-arc oxidation electrolyte, performing micro-arc oxidation treatment, cleaning, and performing annealing treatment to obtain a ceramic oxide film reinforced titanium rod;S3: performing nitriding treatment on the ceramic oxide film reinforced titanium rod, immersing the titanium rod into a sealing sol, impregnating, solidifying, and obtaining the high-hardness rod for ships.The high-hardness corrosion-resistant titanium rod with a dense film layer on the surface is comprehensively prepared by sequentially performing micro-arc oxidation treatment, annealing treatment, pulse plasma nitriding treatment and silicon sol sealing treatment on the titanium rod.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium alloy surface treatment technology, specifically a high-hardness bar for shipbuilding and its preparation method. Background Technology

[0002] Titanium alloys have broad application prospects in the field of marine engineering due to their advantages such as high specific strength, light weight, and resistance to seawater corrosion. However, the low surface hardness and insufficient wear resistance of titanium alloys severely limit their use in high-requirement friction pair components on ships.

[0003] Currently, single methods such as micro-arc oxidation or plasma nitriding are commonly used to strengthen the surface of titanium alloys. However, the ceramic oxide film generated by simple micro-arc oxidation has microporous defects, which allows chloride ions in seawater to easily penetrate the substrate along the pores, inducing pitting corrosion. On the other hand, plasma nitriding alone can make the nitrided layer too hard, which can easily lead to brittleness and cracking.

[0004] Based on this, the present invention proposes a high-hardness bar for shipbuilding and its preparation method, which is of great significance. Summary of the Invention

[0005] The purpose of this invention is to provide a high-hardness bar stock for shipbuilding and its preparation method, so as to solve the related technical problems existing in the prior art.

[0006] A method for preparing high-hardness bar stock for shipbuilding includes the following steps: S1: Using a titanium rod as the substrate, its surface is polished, degreased, and pickled to obtain a pretreated titanium rod. S2: The pretreated titanium rod is immersed in the micro-arc oxidation electrolyte and subjected to micro-arc oxidation treatment to form a micro-arc oxidation film on the surface of the pretreated titanium rod. After cleaning, it is then annealed to obtain a ceramic oxide film reinforced titanium rod. S3: Nitriding treatment is performed on the ceramic oxide film-reinforced titanium rod; then it is immersed in sealing sol, and after impregnation and curing, high hardness rods for shipbuilding are obtained.

[0007] Preferably, after polishing, the surface roughness Ra of the titanium rod is ≤0.8μm.

[0008] Further, the preparation method of the micro-arc oxidation electrolyte is as follows: at room temperature, potassium hydroxide, sodium metasilicate, and sodium aluminate are added to deionized water and stirred for 20-40 minutes; then sodium gluconate, sodium citrate, and disodium ethylenediaminetetraacetate are added and stirred for 20-40 minutes; then cerium nitrate is added and stirred for 10-20 minutes; finally, triethanolamine and ethylene glycol monobutyl ether are added and stirred for 20-40 minutes to obtain the micro-arc oxidation electrolyte.

[0009] Preferably, the micro-arc oxidation electrolyte comprises the following raw material components at the following concentrations: sodium metasilicate 25-35 g / L, sodium aluminate 8-12 g / L, sodium gluconate 4-6 g / L, ethylene glycol monobutyl ether 3-5 g / L, potassium hydroxide 2-3 g / L, cerium nitrate 0.8-1.2 g / L, triethanolamine 1-1.5 g / L, sodium citrate 3-6 g / L, disodium ethylenediaminetetraacetate 1-2 g / L, and deionized water as the solvent.

[0010] More preferably, the process parameters for the micro-arc oxidation treatment are: operating current density 4~8A / dm³. 2 The operating voltage is 420~520V, the duty cycle is 20~30%, the frequency is 500~600Hz, the operating temperature is 25~35℃, and the operating time is 25~35min.

[0011] More preferably, the annealing process parameters are as follows: nitrogen or argon is used as the protective gas, the annealing temperature is 500~650℃, the holding time is 2~4h, and the cooling method is furnace cooling.

[0012] Preferably, the nitriding treatment is carried out using pulsed plasma nitriding technology, with the following process parameters: a mixed gas of N2 and H2 with a volume ratio of 1:(0.3~0.6) is used as the working gas, the working gas pressure is 300~450Pa, the pulse bias voltage is 500~600V, the pulse frequency is 600~1000Hz, the duty cycle is 30~50%, the working temperature is 700~720℃, and the nitriding time is 2~4h.

[0013] More preferably, the preparation method of the sealing sol is as follows: (1) Add anhydrous ethanol and deionized water to the reaction vessel, stir and mix for 5-10 min, then add glacial acetic acid to adjust the pH to 4-5 to obtain the base solution; (2) Add tetraethyl orthosilicate to the base solution while stirring, and continue stirring and mixing for 30-40 min after the addition is complete; then add γ-glycidoxypropyltrimethoxysilane and polyethylene glycol, stir and mix for 40-60 min, and finally let stand for 2-4 h to obtain the sealing sol.

[0014] More preferably, the mass ratio of tetraethyl orthosilicate, γ-glycidyl etheroxypropyltrimethoxysilane, deionized water, anhydrous ethanol, and polyethylene glycol is 1:(0.28~0.55):(0.5~0.7):(2.5~3.5):(0.16~0.22).

[0015] More preferably, the molecular weight of the polyethylene glycol is 400-800.

[0016] More preferably, the impregnation process parameters are: impregnation temperature of 50~60℃ and impregnation time of 20~40min.

[0017] More preferably, the curing process is as follows: first, keep warm at 80~100℃ for 15~30 minutes, then raise the temperature to 140~150℃ and keep warm for 30~60 minutes, and finally let stand at room temperature for 24 hours.

[0018] A second aspect of the present invention provides high-hardness bar stock for ships prepared by the above-described preparation method.

[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention involves micro-arc oxidation of titanium rods to generate a ceramic oxide film on their surface. This ceramic oxide film exhibits higher hardness than the titanium rod itself and also possesses excellent corrosion resistance, significantly improving both the hardness and corrosion resistance of the titanium rod. Furthermore, cerium nitrate is added to the micro-arc oxidation electrolyte used in this invention. Introducing the rare earth metal cerium into the ceramic oxide film refines the ceramic film grains and improves its surface quality, thus positively promoting the hardness and corrosion resistance of the titanium rod.

[0020] 2. The working current density, working voltage, duty cycle, frequency, working temperature, and working time of the micro-arc oxidation process directly affect the porosity and pore size distribution of the ceramic oxide film. In order to retain appropriately interconnected micropores on the ceramic oxide film to facilitate subsequent nitriding, while avoiding excessively large micropores, this invention further controls the process parameters of the micro-arc oxidation process, limiting the working current density to 4~8 A / dm³. 2 The operating voltage is limited to 420~520V, the duty cycle to 20~30%, the frequency to 500~600Hz, the operating temperature to 25~35℃, and the operating time to 25~35min. Within this range of process parameters, it is possible to avoid excessively large and porous or overly dense micropores in the ceramic oxide film, thereby achieving precise construction of a continuously interconnected microporous ceramic oxide film. These microporous channels allow for the diffusion and infiltration of nitrogen atoms during the subsequent pulsed plasma nitriding process.

[0021] 3. In this invention, after micro-arc oxidation, annealing is performed. Annealing can eliminate residual stress inside the ceramic oxide film and avoid cracking of the ceramic oxide film during subsequent nitriding. On the other hand, it can remove electrolyte impurities that may remain in the micropores of the ceramic oxide film and activate the nitriding channels.

[0022] 4. In this invention, the titanium rod reinforced with ceramic oxide film is further subjected to nitriding treatment. Nitrogen atoms can diffuse inward through the micropores of the ceramic oxide film, which can not only strengthen the substrate but also improve the internal porous structure of the ceramic oxide film, significantly enhancing the bonding strength of the ceramic oxide layer. Simultaneously, it greatly improves the hardness and corrosion resistance of the rod. Furthermore, as nitriding proceeds, nitrides gradually deposit in the micropores, thus providing a certain degree of sealing and further improving the corrosion resistance of the titanium rod.

[0023] 5. Since nitriding cannot completely seal the micropores, in order to optimize the corrosion resistance of the titanium rod, a sealing sol is further used to seal the micropores. After sealing, the micropores are almost completely closed, further enhancing the corrosion resistance of the titanium rod. During the preparation of this sealing sol, the molecular weight of polyethylene glycol should be controlled between 400 and 800. An excessively high molecular weight increases the overall viscosity of the sol, thereby reducing capillary permeability and making it difficult to seal the micropores.

[0024] In summary, this invention provides a high-hardness, corrosion-resistant titanium rod with a dense film layer on its surface by sequentially performing micro-arc oxidation, annealing, pulsed plasma nitriding, and silica sol sealing on the titanium rod. Detailed Implementation

[0025] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. It should be understood that the embodiments described herein are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort should fall within the protection scope of the present invention; unless otherwise specified, the raw materials involved are all conventional commercially available products.

[0026] It should be noted that there are no special restrictions on the manufacturers of the raw materials involved in this invention. Exemplary examples include: in the following embodiments, the titanium rod is of grade TC18 and its size is φ85mm × length 165mm; sodium metasilicate; sodium aluminate; sodium gluconate; sodium citrate; disodium ethylenediaminetetraacetate; cerium nitrate; ethylene glycol monobutyl ether; tetraethyl orthosilicate; γ-glycidyl etheroxypropyltrimethoxysilane; polyethylene glycol 600; polyethylene glycol 2000; and other raw materials, all of which are commercially available.

[0027] Alkaline degreasing solution: sodium hydroxide 30g / L, sodium carbonate 25g / L, trisodium phosphate 40g / L, sodium silicate 10g / L, sodium dodecyl sulfate 2g / L, with deionized water as solvent.

[0028] Pickling solution: 40 wt% hydrofluoric acid 40 mL / L, 65 wt% nitric acid 200 mL / L, with deionized water as solvent.

[0029] Example 1: A method for preparing high-hardness bar stock for shipbuilding, comprising the following steps: S1: Polishing, degreasing, and acid washing of the TC18 titanium rod: Using TC18 titanium rod as the substrate, its surface is polished to a surface roughness Ra=0.6μm; then the TC18 titanium rod is placed in an alkaline degreasing solution and immersed at 70℃ for 10min, then removed and rinsed with running water; next, the TC18 titanium rod is placed in an acid pickling solution and immersed at room temperature for 45s, then removed, rinsed with running water, then rinsed with deionized water, and dried with nitrogen to obtain a pretreated TC18 titanium rod. S2: Micro-arc oxidation and annealing treatment of pretreated TC18 titanium rods: S21. Preparation of micro-arc oxidation electrolyte: At room temperature, add potassium hydroxide, sodium metasilicate, and sodium aluminate to deionized water and stir for 30 min; then add sodium gluconate, sodium citrate, and disodium ethylenediaminetetraacetate and stir for 30 min; next, add cerium nitrate and stir for 15 min; finally, add triethanolamine and ethylene glycol monobutyl ether and stir for 30 min to obtain the micro-arc oxidation electrolyte. The micro-arc oxidation electrolyte comprises the following raw material components at the following concentrations: sodium metasilicate 30 g / L, sodium aluminate 10 g / L, sodium gluconate 5 g / L, ethylene glycol monobutyl ether 4 g / L, potassium hydroxide 2.5 g / L, cerium nitrate 1 g / L, triethanolamine 1.3 g / L, sodium citrate 4.5 g / L, disodium ethylenediaminetetraacetate 1.5 g / L, and deionized water as the solvent. S22. Immerse the pretreated TC18 titanium rod in the micro-arc oxidation electrolyte for micro-arc oxidation treatment; The process parameters for micro-arc oxidation are: operating current density 6A / dm³ 2 The operating voltage is 470V, the duty cycle is 25%, the frequency is 550Hz, the operating temperature is 30℃, and the operating time is 30min. S23. Annealing treatment: (1) After micro-arc oxidation treatment, the titanium rod is rinsed with running water, then rinsed with deionized water and dried with nitrogen; (2) Under nitrogen protection, the titanium rod is heated to 570℃ and held for 3 hours, then cooled in the furnace to obtain a ceramic oxide film reinforced titanium rod with a film layer of about 35μm. S3: Nitriding and sealing treatment of ceramic oxide film-reinforced titanium rods: S31: Pulsed plasma nitriding technology is used to nitrid the ceramic oxide film reinforced titanium rod; The nitriding process parameters are as follows: a mixture of N2 and H2 with a volume ratio of 1:0.5 is used as the working gas, the working gas pressure is 350Pa, the pulse bias voltage is 550V, the pulse frequency is 800Hz, the duty cycle is 40%, the working temperature is 710℃, and the nitriding time is 3h. S32: Preparation of sealing sol: (1) Add anhydrous ethanol and deionized water to the reaction vessel and stir for 7.5 min. Then add glacial acetic acid to adjust the pH to 4.5 to obtain the base solution. (2) Add tetraethyl orthosilicate to the base solution while stirring. After the addition is complete, continue stirring for 35 min. Then add γ-glycidoxypropyltrimethoxysilane and polyethylene glycol 600 and stir for 50 min. Finally, let stand for 3 h to obtain the sealing sol. The mass ratio of tetraethyl orthosilicate, γ-glycidoxypropyltrimethoxysilane, deionized water, anhydrous ethanol and polyethylene glycol 600 is 1:0.38:0.6:3:0.18. S33: Sealing treatment: Immerse the nitrided titanium rod in the sealing sol and soak it at 55°C for 30 minutes, then remove it; first keep it at 90°C for 25 minutes, then raise the temperature to 145°C and keep it at 45 minutes, and finally let it stand at room temperature for 24 hours to complete the curing, and obtain high hardness rods for shipbuilding.

[0030] Example 2: A method for preparing high-hardness bar stock for shipbuilding, comprising the following steps: S1: Polishing, degreasing, and acid washing of the TC18 titanium rod: Using TC18 titanium rod as the substrate, its surface is polished to a surface roughness Ra=0.6μm; then the TC18 titanium rod is placed in an alkaline degreasing solution and immersed at 70℃ for 10min, then removed and rinsed with running water; next, the TC18 titanium rod is placed in an acid pickling solution and immersed at room temperature for 45s, then removed, rinsed with running water, then rinsed with deionized water, and dried with nitrogen to obtain a pretreated TC18 titanium rod. S2: Micro-arc oxidation and annealing treatment of pretreated TC18 titanium rods: S21. Preparation of micro-arc oxidation electrolyte: At room temperature, add potassium hydroxide, sodium metasilicate, and sodium aluminate to deionized water and stir for 30 min; then add sodium gluconate, sodium citrate, and disodium ethylenediaminetetraacetate and stir for 30 min; next, add cerium nitrate and stir for 15 min; finally, add triethanolamine and ethylene glycol monobutyl ether and stir for 30 min to obtain the micro-arc oxidation electrolyte. The micro-arc oxidation electrolyte comprises the following raw material components at the following concentrations: sodium metasilicate 25 g / L, sodium aluminate 8 g / L, sodium gluconate 4 g / L, ethylene glycol monobutyl ether 3 g / L, potassium hydroxide 2 g / L, cerium nitrate 0.8 g / L, triethanolamine 1 g / L, sodium citrate 3 g / L, disodium ethylenediaminetetraacetate 1 g / L, and deionized water as the solvent. S22. Immerse the pretreated TC18 titanium rod in the micro-arc oxidation electrolyte for micro-arc oxidation treatment; The process parameters for micro-arc oxidation are: operating current density 4A / dm³2 The operating voltage is 420V, the duty cycle is 20%, the frequency is 500Hz, the operating temperature is 25℃, and the operating time is 25min. S23. Annealing treatment: (1) After micro-arc oxidation treatment, the titanium rod is rinsed with running water, then rinsed with deionized water and dried with nitrogen; (2) Under nitrogen protection, the titanium rod is heated to 500℃ and held for 2 hours, then cooled in the furnace to obtain a ceramic oxide film reinforced titanium rod with a film layer of about 35μm. S3: Nitriding and sealing treatment of ceramic oxide film-reinforced titanium rods: S31: Pulsed plasma nitriding technology is used to nitrid the ceramic oxide film reinforced titanium rod; The nitriding process parameters are as follows: a mixture of N2 and H2 with a volume ratio of 1:0.3 is used as the working gas, the working gas pressure is 300Pa, the pulse bias voltage is 500V, the pulse frequency is 600Hz, the duty cycle is 30%, the working temperature is 700℃, and the nitriding time is 2h. S32: Preparation of sealing sol: (1) Add anhydrous ethanol and deionized water to the reaction vessel and stir for 7.5 min. Then add glacial acetic acid to adjust the pH to 4.5 to obtain the base solution. (2) Add tetraethyl orthosilicate to the base solution while stirring. After the addition is complete, continue stirring for 35 min. Then add γ-glycidoxypropyltrimethoxysilane and polyethylene glycol 600 and stir for 50 min. Finally, let stand for 3 h to obtain the sealing sol. The mass ratio of tetraethyl orthosilicate, γ-glycidoxypropyltrimethoxysilane, deionized water, anhydrous ethanol and polyethylene glycol 600 is 1:0.28:0.5:2.5:0.16. S33: Sealing treatment: Immerse the nitrided titanium rod in the sealing sol and soak it at 50°C for 20 minutes, then remove it; first keep it at 80°C for 15 minutes, then raise the temperature to 140°C and keep it at 140°C for 30 minutes, and finally let it stand at room temperature for 24 hours to complete the curing and obtain high hardness rods for shipbuilding.

[0031] Example 3: A method for preparing high-hardness bar stock for shipbuilding, comprising the following steps: S1: Polishing, degreasing, and acid washing of the TC18 titanium rod: Using TC18 titanium rod as the substrate, its surface is polished to a surface roughness Ra=0.6μm; then the TC18 titanium rod is placed in an alkaline degreasing solution and immersed at 70℃ for 10min, then removed and rinsed with running water; next, the TC18 titanium rod is placed in an acid pickling solution and immersed at room temperature for 45s, then removed, rinsed with running water, then rinsed with deionized water, and dried with nitrogen to obtain a pretreated TC18 titanium rod. S2: Micro-arc oxidation and annealing treatment of pretreated TC18 titanium rods: S21. Preparation of micro-arc oxidation electrolyte: At room temperature, add potassium hydroxide, sodium metasilicate, and sodium aluminate to deionized water and stir for 30 min; then add sodium gluconate, sodium citrate, and disodium ethylenediaminetetraacetate and stir for 30 min; next, add cerium nitrate and stir for 15 min; finally, add triethanolamine and ethylene glycol monobutyl ether and stir for 30 min to obtain the micro-arc oxidation electrolyte. The micro-arc oxidation electrolyte comprises the following raw material components at the following concentrations: sodium metasilicate 35 g / L, sodium aluminate 12 g / L, sodium gluconate 6 g / L, ethylene glycol monobutyl ether 5 g / L, potassium hydroxide 3 g / L, cerium nitrate 1.2 g / L, triethanolamine 1.5 g / L, sodium citrate 6 g / L, disodium ethylenediaminetetraacetate 2 g / L, and deionized water as the solvent. S22. Immerse the pretreated TC18 titanium rod in the micro-arc oxidation electrolyte for micro-arc oxidation treatment; The process parameters for micro-arc oxidation are: operating current density 8A / dm³ 2 The operating voltage is 520V, the duty cycle is 30%, the frequency is 600Hz, the operating temperature is 35℃, and the operating time is 35min. S23. Annealing treatment: (1) After micro-arc oxidation treatment, the titanium rod is rinsed with running water, then rinsed with deionized water and dried with nitrogen; (2) Under nitrogen protection, the titanium rod is heated to 650℃ and held for 4 hours, then cooled in the furnace to obtain a ceramic oxide film reinforced titanium rod with a film layer of about 35μm. S3: Nitriding and sealing treatment of ceramic oxide film-reinforced titanium rods: S31: Pulsed plasma nitriding technology is used to nitrid the ceramic oxide film reinforced titanium rod; The nitriding process parameters are as follows: a mixture of N2 and H2 with a volume ratio of 1:0.6 is used as the working gas, the working gas pressure is 450Pa, the pulse bias voltage is 600V, the pulse frequency is 1000Hz, the duty cycle is 50%, the working temperature is 720℃, and the nitriding time is 4h. S32: Preparation of sealing sol: (1) Add anhydrous ethanol and deionized water to the reaction vessel and stir for 7.5 min. Then add glacial acetic acid to adjust the pH to 4.5 to obtain the base solution. (2) Add tetraethyl orthosilicate to the base solution while stirring. After the addition is complete, continue stirring for 35 min. Then add γ-glycidoxypropyltrimethoxysilane and polyethylene glycol 600 and stir for 50 min. Finally, let stand for 3 h to obtain the sealing sol. The mass ratio of tetraethyl orthosilicate, γ-glycidoxypropyltrimethoxysilane, deionized water, anhydrous ethanol and polyethylene glycol 600 is 1:0.55:0.7:3.5:0.22. S33: Sealing treatment: Immerse the nitrided titanium rod in the sealing sol and soak it at 60°C for 40 minutes, then remove it; first keep it at 100°C for 30 minutes, then raise the temperature to 150°C and keep it at 60 minutes, and finally let it stand at room temperature for 24 hours to complete the curing, and obtain high hardness rods for shipbuilding.

[0032] The following is a control experiment based on Example 1, with comparative examples 1 to 8, as detailed below: Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustment: micro-arc oxidation treatment is omitted, while other processes remain unchanged. Specifically: S2: Annealing treatment of pretreated TC18 titanium rods: Under nitrogen protection, the pretreated TC18 titanium rod was heated to 570℃ and held for 3 hours, then furnace cooled. Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustment: annealing is not performed, while other processes remain unchanged. Specifically: S2: Micro-arc oxidation treatment of pretreated TC18 titanium rods: S21. Preparation of micro-arc oxidation electrolyte: At room temperature, add potassium hydroxide, sodium metasilicate, and sodium aluminate to deionized water and stir for 30 min; then add sodium gluconate, sodium citrate, and disodium ethylenediaminetetraacetate and stir for 30 min; next, add cerium nitrate and stir for 15 min; finally, add triethanolamine and ethylene glycol monobutyl ether and stir for 30 min to obtain the micro-arc oxidation electrolyte. The micro-arc oxidation electrolyte comprises the following raw material components at the following concentrations: sodium metasilicate 30 g / L, sodium aluminate 10 g / L, sodium gluconate 5 g / L, ethylene glycol monobutyl ether 4 g / L, potassium hydroxide 2.5 g / L, cerium nitrate 1 g / L, triethanolamine 1.3 g / L, sodium citrate 4.5 g / L, disodium ethylenediaminetetraacetate 1.5 g / L, and deionized water as the solvent. S22. The pretreated TC18 titanium rod is immersed in the micro-arc oxidation electrolyte for micro-arc oxidation treatment. After the treatment, the TC18 titanium rod is rinsed with running water, then rinsed with deionized water, and dried with nitrogen to obtain a ceramic oxide film-reinforced titanium rod with a film layer of about 35 μm. The process parameters for micro-arc oxidation are: operating current density 6A / dm³ 2 The operating voltage is 470V, the duty cycle is 25%, the frequency is 550Hz, the operating temperature is 30℃, and the operating time is 30min.

[0033] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following adjustment: nitriding treatment is not performed, while other processes remain unchanged. Specifically: S3: Sealing treatment of ceramic oxide film-reinforced titanium rods: S31: Preparation of sealing sol: (1) Add anhydrous ethanol and deionized water to the reaction vessel and stir for 7.5 min. Then add glacial acetic acid to adjust the pH to 4.5 to obtain the base solution. (2) Add tetraethyl orthosilicate to the base solution while stirring. After the addition is complete, continue stirring for 35 min. Then add γ-glycidoxypropyltrimethoxysilane and polyethylene glycol 600 and stir for 50 min. Finally, let stand for 3 h to obtain the sealing sol. The mass ratio of tetraethyl orthosilicate, γ-glycidoxypropyltrimethoxysilane, deionized water, anhydrous ethanol and polyethylene glycol 600 is 1:0.38:0.6:3:0.18. S32: Sealing treatment: Immerse the annealed titanium rod in the sealing sol and soak it at 55°C for 30 minutes, then take it out; first keep it at 90°C for 25 minutes, then raise the temperature to 145°C and keep it at 45 minutes, and finally let it stand at room temperature for 24 hours to complete the curing and obtain high hardness rods for ships.

[0034] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustment: no sealing treatment is performed, while other processes remain unchanged. Specifically: S3: Nitriding treatment of titanium rods reinforced with ceramic oxide film: Pulsed plasma nitriding technology was used to nitrid ceramic oxide film-reinforced titanium rods to obtain high-hardness rods for shipbuilding. The nitriding process parameters are as follows: a mixture of N2 and H2 with a volume ratio of 1:0.5 is used as the working gas, the working gas pressure is 350Pa, the pulse bias voltage is 550V, the pulse frequency is 800Hz, the duty cycle is 40%, the working temperature is 710℃, and the nitriding time is 3h.

[0035] Comparative Example 5: Comparative Example 5 is based on Example 1, with the following adjustment: cerium nitrate is not added to the micro-arc oxidation electrolyte, while other processes remain unchanged. Specifically: S2: Micro-arc oxidation and annealing treatment of pretreated TC18 titanium rods: S21. Preparation of micro-arc oxidation electrolyte: At room temperature, add potassium hydroxide, sodium metasilicate, and sodium aluminate to deionized water and stir for 30 min; then add sodium gluconate, sodium citrate, and disodium ethylenediaminetetraacetate and stir for 30 min; then add triethanolamine and ethylene glycol monobutyl ether and stir for 30 min to obtain the micro-arc oxidation electrolyte. The micro-arc oxidation electrolyte comprises the following raw material components at the following concentrations: sodium metasilicate 30 g / L, sodium aluminate 10 g / L, sodium gluconate 5 g / L, ethylene glycol monobutyl ether 4 g / L, potassium hydroxide 2.5 g / L, triethanolamine 1.3 g / L, sodium citrate 4.5 g / L, disodium ethylenediaminetetraacetate 1.5 g / L, and deionized water as the solvent.

[0036] Comparative Example 6: Comparative Example 6 is based on Example 1, but the process parameters of the micro-arc oxidation treatment were adjusted, while other processes remained unchanged. Specifically: S22. Immerse the pretreated TC18 titanium rod in the micro-arc oxidation electrolyte for micro-arc oxidation treatment; The process parameters for micro-arc oxidation are: operating current density 10A / dm³ 2 The operating voltage is 550V, the duty cycle is 35%, the frequency is 650Hz, the operating temperature is 30℃, and the operating time is 40min.

[0037] Comparative Example 7: Comparative Example 7 is based on Example 1, with the following adjustment: the molecular weight of polyethylene glycol in the sealing sol is 2000, while other processes remain unchanged. Specifically: S32: Preparation of sealing sol: (1) Add anhydrous ethanol and deionized water to the reaction vessel and stir for 7.5 min. Then add glacial acetic acid to adjust the pH to 4.5 to obtain the base solution. (2) Add tetraethyl orthosilicate to the base solution while stirring. After the addition is complete, continue stirring for 35 min. Then add γ-glycidoxypropyltrimethoxysilane and polyethylene glycol 2000 and stir for 50 min. Finally, let stand for 3 h to obtain the sealing sol. The mass ratio of tetraethyl orthosilicate, γ-glycidoxypropyltrimethoxysilane, deionized water, anhydrous ethanol and polyethylene glycol 2000 is 1:0.38:0.6:3:0.18.

[0038] Comparative Example 8: Comparative Example 8 is based on Example 1, with the following adjustment: only the TC18 titanium rod is polished to a surface roughness of Ra = 0.6 μm, and no other treatment is performed.

[0039] Performance testing: The rods prepared in Examples 1-3 and Comparative Examples 1-8 were subjected to hardness and corrosion resistance tests. The specific test methods are as follows: (1) Hardness test: A microhardness tester was used to apply a 100g load to the bar for 20s; (2) Corrosion resistance test: The rods were placed in a salt spray test chamber for corrosion resistance testing; the test conditions were: test temperature 35℃, corrosive medium 5wt% NaCl aqueous solution with pH=7.0, and salt spray deposition rate 2mL / (80cm). 2 •h); Record the time when visible pits / white spots are first observed with the naked eye, and observe once every 12 hours.

[0040] The test results are shown in Table 1 below: Table 1

[0041] Results Analysis: As can be seen from the test results in Table 1 above, the present invention has prepared a high-hardness corrosion-resistant titanium rod with a dense film layer by sequentially performing micro-arc oxidation treatment, annealing treatment, pulsed plasma nitriding treatment, and silica sol sealing treatment on the titanium rod. Each process is indispensable.

[0042] For those skilled in the art, the present invention is obviously not limited to the details disclosed in the exemplary embodiments described above. The present invention can be implemented in other specific ways without departing from its spirit and essential characteristics. Therefore, the foregoing embodiments should be considered exemplary rather than restrictive from any perspective. The scope of protection of the present invention is defined by the appended claims. Therefore, all variations falling within the meaning and scope of the equivalent elements of the claims should be attributed to the scope of the present invention.

Claims

1. A method for preparing high-hardness bar stock for shipbuilding, characterized in that: Includes the following steps: S1: Using a titanium rod as the substrate, its surface is polished, degreased, and pickled to obtain a pretreated titanium rod. S2: The pretreated titanium rod is immersed in the micro-arc oxidation electrolyte for micro-arc oxidation treatment; Cleaning and annealing yields ceramic oxide film-reinforced titanium rods. S3: Nitriding treatment is performed on the ceramic oxide film-reinforced titanium rod; it is then immersed in sealing sol, impregnated, and cured to obtain high-hardness rods for shipbuilding. The micro-arc oxidation electrolyte comprises the following raw material components at the following concentrations: sodium metasilicate 25-35 g / L, sodium aluminate 8-12 g / L, sodium gluconate 4-6 g / L, ethylene glycol monobutyl ether 3-5 g / L, potassium hydroxide 2-3 g / L, cerium nitrate 0.8-1.2 g / L, triethanolamine 1-1.5 g / L, sodium citrate 3-6 g / L, disodium ethylenediaminetetraacetate 1-2 g / L, and deionized water as the solvent.

2. The method for preparing a high-hardness bar stock for shipbuilding according to claim 1, characterized in that: The process parameters for the micro-arc oxidation treatment are: operating current density 4~8A / dm³. 2 The operating voltage is 420~520V, the duty cycle is 20~30%, the frequency is 500~600Hz, the operating temperature is 25~35℃, and the operating time is 25~35min.

3. The method for preparing a high-hardness bar stock for shipbuilding according to claim 1, characterized in that: The annealing process parameters are as follows: nitrogen or argon is used as the protective gas, the annealing temperature is 500~650℃, the holding time is 2~4h, and the cooling method is furnace cooling.

4. The method for preparing high-hardness bar stock for shipbuilding according to claim 1, characterized in that: The nitriding treatment is carried out using pulsed plasma nitriding technology. The process parameters are as follows: a mixed gas of N2 and H2 with a volume ratio of 1:(0.3~0.6) is used as the working gas; the working gas pressure is 300~450Pa; the pulse bias voltage is 500~600V; the pulse frequency is 600~1000Hz; the duty cycle is 30~50%; the working temperature is 700~720℃; and the nitriding time is 2~4h.

5. The method for preparing high-hardness bar stock for shipbuilding according to claim 1, characterized in that: The method for preparing the sealing sol is as follows: Anhydrous ethanol and deionized water are stirred and mixed, then glacial acetic acid is added to adjust the pH to 4-5; under stirring, tetraethyl orthosilicate is added dropwise, and after the addition is complete, stirring and mixing are continued; then γ-glycidoxypropyltrimethoxysilane and polyethylene glycol are added, stirred and mixed, and allowed to stand to obtain the sealing sol; The mass ratio of tetraethyl orthosilicate, γ-glycidyl etheroxypropyltrimethoxysilane, deionized water, anhydrous ethanol, and polyethylene glycol is 1:(0.28~0.55):(0.5~0.7):(2.5~3.5):(0.16~0.22).

6. The method for preparing a high-hardness bar stock for shipbuilding according to claim 5, characterized in that: The molecular weight of the polyethylene glycol is 400-800.

7. The method for preparing high-hardness bar stock for shipbuilding according to claim 1, characterized in that: The impregnation process parameters are as follows: impregnation temperature is 50~60℃, and impregnation time is 20~40min; the curing process is as follows: first, keep warm at 80~100℃ for 15~30min, then raise the temperature to 140~150℃ and keep warm for 30~60min, and finally let stand at room temperature for 24h.

8. The method for preparing high-hardness bar stock for shipbuilding according to claim 1, characterized in that: The preparation method of the micro-arc oxidation electrolyte is as follows: add potassium hydroxide, sodium metasilicate, and sodium aluminate to deionized water and stir to mix; then add sodium gluconate, sodium citrate, and disodium ethylenediaminetetraacetate and stir to mix; then add cerium nitrate and stir to mix; finally add triethanolamine and ethylene glycol monobutyl ether and stir to mix to obtain the micro-arc oxidation electrolyte.

9. The method for preparing a high-hardness bar stock for shipbuilding according to claim 1, characterized in that: After polishing, the surface roughness Ra of the titanium rod is ≤0.8μm.

10. A high-hardness bar stock for shipbuilding, characterized in that: It is prepared by any one of the preparation methods described in claims 1 to 9.